Intersection syndrome in an NCAA division I women`s softball player: a case study - Burt, J.; Zwart, M. B.; Roiger, T. C. (International Journal of Athletic Therapy & Training, 2017)
An 18-year-old NCAA Division I women`s softball player presented with a sudden onset of pain in her left wrist during a strength and conditioning workout. Initial examination revealed pain, loss of AROM, decreased muscle strength, and paresthesia. The patient experienced symptomology for 12+ weeks. Corticosteroid injections were administered which finally confirmed diagnosis, reduced pain, and paresthesia. Intersection syndrome is generally an overuse condition which resolves within approximately 2 weeks. This case demonstrates that examination findings, imaging, immobilization, and a therapeutic exercise plan may not be sufficient to decrease patient symptomology.